Economic growth : theory, empirics and policy - Valdés, Benigno (Northampton, Ma. : Edward Elgar, 1999)
Economic Growth is an advanced undergraduate text written specifically for one semester courses in growth theory and for first year graduate students to refresh their knowledge. It will also be of great use for scholars and professional economists as the text contains many references to practical policy issues. The author condenses the fundamental issues of growth theory and covers the new ideas in a highly entertaining text, written in a clear and accessible style.
Includes bibliographical references and index.
lje 23/08/16
Loan
Keywords: Economic development; Economic policy